Understanding The Behavior and Perceptions of Millennial Generation as Guidance in Developing Service Products and Marketing Strategies: Evidence from West Java, Indonesia - Daduk Merdika Mansur; Liestyowati Liestyowati; Ahmad Fauzi Maryadi; Christanto Triwibisono (Jurnal Manajemen Bisnis, 2022)
This study aims to determine the behavior of the millennial generation in Indonesia, which is experiencing high business growth. Understanding the behavior and perceptions of the millennial generation can be an important factor as guidance or evidence in developing service products and marketing strategies that are carried out. This study uses a qualitative survey method by distributing online surveys. Data processing is carried out using the theme analytic method to describe the important factors that become the perception and behavior of the millennial generation in Indonesia. Findings: The widespread use of the internet in Indonesia has shifted the behavior and lifestyle of the younger generation. The number of entertainment facilities and the strong interaction on social media have shaped the perception and behavior of the millennial generation in Indonesia. Characters who live relaxed and always want to have fun are the big picture of the profile of the younger generation. Aspects of literacy or learning are also increasing by referring to things related to knowledge about problem solving. The need for a harmonious relationship is more missed than the rewards of materialism as an indication of the millennial generation's longing to have a warm relationship with their parents. The use of free time is more focused on fun activities that are relaxing. The thing that becomes an important memory led to a desire in an atmosphere of harmony. The anxiety that is felt hopes to get more attention from parents. Heavy mental pressure raises the need for sharing quite high and frequency every day.